Comparative study using different methods for calculating contact tensions in spur gears - Ramos-Botello, Yoan Manuel (2022)
One of the most common causes of failure in gear drives is known as surface fatigue or pitting. To predict the behaviour of the material against this phenomenon, international design standards, the American Gear Manufacturing Association (AGMA) and the International Organization for Standardization (ISO), formulate models based on the Hertz pressure distribution, for the contact between solids. In this research, contact stresses are compared in straight-tooth cylindrical gears, in accordance with the provisions of the aforementioned standards, the Hertz criterion and through the finite element method. The three-dimensional models were obtained with the help of a computer-aided design (CAD) package, where the specifications of each standard were taken into account. As one of the calculation variants to compare, it is the result obtained by numerical simulation, only the factors that depend of the tooth geometry and its material will be taken into account. The results obtained were analyzed statistically, where the effectiveness of the finite element method for this type of calculation was determined, in addition, these are more similar to those obtained by the Hertz method, which is the theory that serves as the basis for the aforementioned standards.